Personnel Mobility and Organizational Performance: The Effects of Specialist vs. Generalist Experience and Organizational Work Structure - Fahrenkopf, Erin; Guo, Jerry; Argote, Linda (Organization Science, 2020)
This study advances understanding of the conditions under which a new worker improves organizational performance. We argue that the extent to which new group members have experience working as specialists or generalists is a critical factor in explaining performance after the new member joins. We conceptualize specialists as those who concentrate on a particular component of an organization’s task, whereas generalists perform all components of the task. As such, a specialist must coordinate with other group members to complete the group’s task, which makes a specialist more interdependent with other members and in possession of more organization-specific knowledge than a generalist. We predict that (1) groups receiving specialist new members do not perform as well after the new member joins as compared with groups receiving generalist new members and (2) groups with new members whose work experience and recipient group structure are aligned (i.e., generalist movers into generalist groups and specialist movers into specialist groups) perform better than groups with new members whose experience and recipient group structure are not aligned. We test our hypotheses using a laboratory study in which we manipulate the extent to which new members and incumbent members of recipient groups work as specialists or generalists. Participants work as generalists or specialists in three-person groups and receive a new member who acquired experience as a specialist or generalist in another group. We find support for our hypotheses and provide evidence on mechanisms through which potential new members’ backgrounds enable them to contribute significantly to their recipient groups. New members who acquire experience in a structure similar to that of their recipient organizations report that they experience greater fit with their new groups, which enables their recipient groups to perform better than groups where new members’ experience and recipient group structure are not aligned. Additionally, our results suggest generalists may be more likely than specialists to transfer knowledge to their new groups.